Spectrum of CFTR mutations in Chechen cystic fibrosis patients: high frequency of c.1545_1546delTA (p.Tyr515X; 1677delTA) and c.274G>A (p.Glu92Lys, E92K) mutations in North Caucasus - Petrova, N V; Kashirskaya, N Y; Saydaeva, D K; Polyakov, A V; Adyan, T A; Simonova, O I; Gorinova, Y V; Kondratyeva, E I; Sherman, V D; Novoselova, O G; Vasilyeva, T A; Marakhonov, A V; et al. (Bmc medical genetics, 2019)
BACKGROUND: Cystic fibrosis (CF; OMIM #219700) is a common autosomal recessive disease caused by pathogenic variants (henceforward mutations) in the cystic fibrosis transmembrane conductance regulator gene (CFTR). The spectrum and frequencies of CFTR mutations vary among different populations. Characterization of the specific distribution of CFTR mutations can be used to optimize genetic counseling, foster reproductive choices, and facilitate the introduction of mutation-specific therapies. Chechens are a distinct Caucasian ethnic group of the Nakh peoples that originated from the North Caucasus. Chechens are one of the oldest ethnic groups in the Caucasus, the sixth largest ethnic group in the Russian Federation (RF), and constitute the majority population of the Chechen Republic (Chechnya). The spectrum of CFTR mutations in a representative cohort of Chechen CF patients and healthy individuals was analyzed. METHODS: Molecular genetic analysis of 34 CFTR mutations (representing approx. 80-85% of mutations in multiethnic CF populations of the RF) was performed in 32 CF patients from 31 unrelated Chechen families living in Chechnya. One hundred randomly chosen healthy Chechens were analyzed for the 15 most common "Russian" mutations. The clinical symptoms in Chechen CF patients with different CFTR genotypes were investigated. RESULTS: High frequencies of c.1545_1546delTA (p.Tyr515X; 1677delTA) (52 out of 64 CFTR alleles tested; 81.3%) and c.274G > A (p.Glu92Lys, E92K) (8/64, 12.5%) mutations were found. Twenty patients were homozygous for the c.1545_1546delTA mutation, and eight were compound heterozygous for the c.1545_1546delTA and c.274G > A mutations. Three carriers of the c.1545_1546delTA mutation were also found in the cohort of 100 apparently healthy Chechens (frequency - 0.015). The c.1545_1546delTA and c.274G > A mutations are linked to the same haplotype (22-7-16-13) of intragenic Short Tandem Repeat markers, i.e., IVS1CA, IVS6aGATT, IVS8CA, and IVS17bCA. CONCLUSIONS: The distribution of CFTR mutations in the Chechen CF population is unique regarding the high frequency of mutations c.1545_1546delTA and c.274G > A (more than 90% of the mutant alleles). The c.274G > A mutation is associated with a less severe course of CF than that observed in c.1545_1546delTA homozygotes. Testing for these two variants can be proposed as the first step of CF DNA diagnosis in the Chechen population.
Keywords: genetická predispozice k nemoci; dítě; mladiství; Gene Frequency; Point Mutation; protein CFTR; frekvence genu; Case-Control Studies; Genetic Predisposition to Disease; Russia; Rusko; Cystic Fibrosis; Infant, Newborn; stupeň závažnosti nemoci; Male; bodová mutace; studie případů a kontrol; lidé; Severity of Illness Index; novorozenec; Cystic Fibrosis Transmembrane Conductance Regulator; cystická fibróza; Adolescent; Child, Preschool; ženské pohlaví; časná diagnóza; Infant; kojenec; Early Diagnosis; mužské pohlaví; předškolní dítě; sekvenční delece; Child; Sequence Deletion; Humans; Female